Menelusuri Akuntansi Biaya Pengolahan Limbah Plastik dalam Perspektif Sustainability - Taufik Afdal; Nina Yusnita Yamin; Ernawaty Usman; Rahmi Syafitri (SAFE-Network, 2026)
This study aims to explore and analyze the cost structure of plastic waste processing through a sustainability perspective. The case study was conducted at the waste processing unit of the Central Sulawesi Provincial Environmental Agency from April to December 2025, to understand the economic efficiency behind environmental conservation efforts. Using a descriptive approach with the Activity-Based Costing (ABC) method, this study identified and allocated costs based on actual resource-consuming activities. Data were collected through field observations, interviews, and operational documentation. The results indicate that the main activities include collection, sorting, production through pyrolysis, feasibility testing, and machine maintenance. With a total processing cost of IDR 44,590,100, 283.93 liters of fuel oil were produced, resulting in a production cost of IDR 157,046 per liter. The largest burden lies in collection activities. Meanwhile, the production process is heavily dominated by energy consumption. Holistically, although current production costs are relatively high, from a sustainability perspective, this initiative proves its significance in three pillars of sustainability: the environmental aspect through reducing the waste burden, the economic aspect through creating new value, and the social aspect through empowering local communities. The results of this study imply that plastic waste management has the potential to be developed sustainably through increased operational efficiency and optimization of production scale, including the use of technology in plastic waste processing.